PENGARUH KEMANDIRIAN BELAJAR DAN SARANA PRASARANA PEMBELAJARAN TERHADAP HASIL BELAJAR PRAKTIK DI SMK NEGERI 2 TUBAN - Mujisuciningtyas, Nunuk (UNIVERSITAS NEGERI SURABAYA, 2014)
This study aims to determine the effect of independent learning and Learning Infrastructure on learning outcomes of students in class XII SMK Negeri 2 Tuban. Population XII class field of study Business and Management expertise, skill competency Marketing, Accounting and Office Administration 2013/2014 school year as many as 284 students. The study sample as many as 166 students are set with purporsional random sampling technique. Data were collected using questionnaires, documentation, observations and interviews. Using a quantitative approach. With Test classical assumption of normality test, multicollinearity, heteroscedasticity test, linearity test. The results of the analysis obtained by partial t test both variables have a significant effect with a significant level of 0.000 is less than 0.05. Simultaneously also have a significant effect on learning outcomes of students practice with a significant level of 0.000 is less than 0.05